Characterization of astrocyte subpopulations after hypoxia in vitro - Courbassier, Natália Rodrigues [UNIFESP] (2023)
Astrocytes become reactive after a Central Nervous System (CNS) injury, passing by phenotypic changes (mainly hypertrophy and gene expression modifications), which can include proliferation and dedifferentiation. Physiologically, astrocytes are very heterogenous cells, they can vary according to region, layer location, morphology, age,and others. Given their heterogeneity, a growing body of literature has been sought to unravel astrocytespecific functions and signatures. Such heterogeneity extends to their reactive state, which is not a uniform response but rather possesses high complexity varying according to stimulus nature and intensity. Previously, our Lab described Notch signaling activation on astrocyte reactivity in vivo and in vitro of brain damage by traumatic brain injury. In addition, we studied the influence of several biomaterials' stiffness on astrocyte reactivity and their morphological response in vitro. In both studies reactive astrocytes showed an aggregation pattern characterized by nonhomogeneous distribution at culture dish. Here, we sought to evaluate whether hypoxia would promote astrocyte reactivity and induce their aggregation in vitro. Further, we characterized astrocyte subpopulation profiles considering their maturity state and expression of reactive protein markers. The brain is one of the most sensitive organs to hypoxia due to its high energy supply required to maintain its proper function. Hypoxia/ischemia have been extensively used as an experimental target in a wide range of studies. However, there is a lack of hypoxia outcome itself, a condition observed in perinatal hypoxia. Here, we observed morphological changes after hypoxia. However, gene expression of the main reactivity markers of astrocytes remained unaltered. For the first time we described an astrocytes aggregation pattern in vitro in response to hypoxia. The molecular and cellular characterization of astrocytes in physiological and pathological conditions can provide higher comprehension about their role in health and disease, such knowledge can uncover mechanisms that underlies its response to achieve regenerative medicine advances.